Lattice relaxation effect in CsxMA(1-x)PbBr3 single crystal to enhance optoelectronic performance of perovskite photodetectors. Issue 1 (1st January 2022) - Li, Lei; Su, Mengwei; Qiu, Xin; Zhao, Xinyu; Zhu, Xinglin; Wei, Wenwang; Huang, Lixiang; Li, Guoxin; Wang, Yukun; Sun, W.H.
Abstract: Single crystal (SC) MAPbBr3 perovskite is regarded as a promising material to fabricate high-performance photodetectors (PDs) due to its impressive optoelectronic properties and good chemical stability. Cs + doping has been proved to be an effective method to significantly improve the optoelectronic properties of MAPbBr3 SC. However, the intrinsic effect of Cs + on the crystal structure is still unclear. Herein, we grew a series Csx MA(1-x) PbBr3 SCs. X-ray rocking curves (XRC) of Csx MA(1-x) PbBr3 SCs prove that appropriate Cs-doping concentration could reduce defect density effectively. X-ray photoelectron spectroscopy (XPS) measurements indicate that Cs-doping enhances the atoms interaction in Csx MA(1-x) PbBr3 lattice due to isoelectronic impurity effect. Single-crystal PDs were fabricated to compare the optoelectronic properties of MAPbBr3 SCs with different Cs-doping concentration, and the 2% Cs-doped Csx MA(1-x) PbBr3 PD shows the optimum performance. Density functional theory (DFT) calculations demonstrate that Cs-doping leads to lattice relaxation effect which is benefit to reduce trap density of Csx MA(1-x) PbBr3 SCs. The Pb-6p level of Csx MA(1-x) PbBr3 slightly shifts to lower energy region compared with MAPbBr3, resulting in the decrease of band gap of Csx MA(1-x) PbBr3 .